2005
DOI: 10.1021/cm048622x
|View full text |Cite
|
Sign up to set email alerts
|

Organic−Inorganic Poly(Methyl Methacrylate) Hybrids with Confined Polyhedral Oligosilsesquioxane Macromonomers

Abstract: We herein report the synthesis of organic−inorganic hybrid poly(methyl methacrylate) containing polyhedral oligosilsesquioxanes. Octakis(3-hydroxypropyldimethylsiloxy)octasilsesquioxane (OHPS) was synthesized from octakis(hydridodimethylsiloxy)octasilsesquioxane [Si8O12(OSiMe2H)8, Q8M8 H] following literature procedures. Octakis(methacryloxypropyldimethylsiloxy) octasilsesquioxane (OMPS) was synthesized via the reaction of methacryloyl chloride or methacrylic acid anhydride with OHPS, with the latter giving im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…14 Toepfer et al observed an increase of T g in PMMA-POSS hybrids. 15 Kopesky et al analyzed viscosity data in PMMA-POSS, tethered and untethered, and found a significant slowing down of chain relaxation in the first case and a decrease of viscosity, correlated with an increase of free volume, in the second case. 16 Epoxy networks modified by POSS were prepared (often by using multifunctional epoxy-POSS monomers 5,8 ) and investigated by several researchers.…”
Section: Introductionmentioning
confidence: 99%
“…14 Toepfer et al observed an increase of T g in PMMA-POSS hybrids. 15 Kopesky et al analyzed viscosity data in PMMA-POSS, tethered and untethered, and found a significant slowing down of chain relaxation in the first case and a decrease of viscosity, correlated with an increase of free volume, in the second case. 16 Epoxy networks modified by POSS were prepared (often by using multifunctional epoxy-POSS monomers 5,8 ) and investigated by several researchers.…”
Section: Introductionmentioning
confidence: 99%
“…100 It has also been shown that POSS can effectively act as a nano cross-linking agent, provided it has been functionalized, producing hybrid materials with superb structural and physical properties. 101,102 In these studies, highly cross-linked PMMA-POSS hybrids were developed by functionalizing POSS with methacryloyl groups via methacrylic acidanhydride 101 or modification of POSS-PEG with methacryloyl chloride 102 and then reacting with methacrylic monomer. Figure 15 shows all the possible structures and incorporation methods of POSS into polymer chains.…”
Section: Poss-based Hybridsmentioning
confidence: 99%
“…Recently, some works on dendritic ligands based on cages, for example, β-diketone, carboxyl, and their complexes with some rare earth ions have been successfully prepared. [13][14][15] Multimethacrylate substituted cages have been synthesized by different methods, such as hydrosilylation, 16 nucleophilic substitution 17 and hydrolytic condensation, 18 and some hybrid nanocomposites have been prepared from these cage monomers via thermal polymerization [19][20][21][22] or photopolymerization. 23,24 However, these cage compounds have not been used as a ligand to coordinate with rare earth ion to form a hybrid complex containing polymerizable methacrylate group.…”
Section: Introductionmentioning
confidence: 99%